Large-eddy simulation of an annular-sector duct rotating in parallel mode - Daroz, Vinicius (2018)
In this research the turbulent flow within an annular-sector duct rotating about a parallel axis is numerically solved using large-eddy simulation (LES). The study is motivated by the lack of in-depth understanding of the interplay between rotation- and shear-induced phenomena over turbulence-related quantities for a problem that has vast applicability in rotating machinery and internal cooling systems. As a first approach, the solution of the problem is performed with the aid of a commercial computational fluid dynamics (CFD) code. The numerical procedure and solution methodology were verified against reference solution data in order to grant reliability to the obtained results. The annular-sector problem was investigated by means of hydrodynamical and geometrical parameters. First, the swirl parameter, which represents the ratio of rotational to axial Reynolds number, was found to cause substantial change in the mean flow profiles and turbulent quantities. Interestingly, increasing rotation promotes a stabilising effect in the flow bulk region. On the other hand, rotation increases the overall friction factor. The duct apex angle effect was found to alter both primary and secondary motion patterns. The ratio of the inner to outer radius influence resembles that of the apex angle. Intriguingly, the friction factor presented a minimum point suggesting that an optimal hydrodynamical configuration may be obtained.